2017
DOI: 10.1039/c6cp08015d
|View full text |Cite
|
Sign up to set email alerts
|

Polarization loss in the organic ferroelectric trialkylbenzene-1,3,5-tricarboxamide (BTA)

Abstract: We investigate the polarization loss in the archetypical molecular organic ferroelectric trialkylbenzene-1,3,5-tricarboxamide (BTA). We prove that the polarization loss is due to thermally activated R-relaxation, which is a collective reversal of the amide dipole moments in ferroelectric domains. By applying a weak electrostatic field both the polarization loss and the R-relaxation are suppressed, leading to an enhancement of the retention time by at least several orders of magnitude. Alternative loss mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Therefore, we performed direct electrical polarization relaxation measurements on metal/ferroelectric/metal devices at different temperatures. [50] As an example, the polarization decay for all materials at 70 °C is shown in Figure 3a; a full data set can be found in Figure S5 (Supporting Information). Indeed, Figure 3a clearly shows enhanced retention with changing the alkyl chain length from 18 to 6 carbon atoms.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we performed direct electrical polarization relaxation measurements on metal/ferroelectric/metal devices at different temperatures. [50] As an example, the polarization decay for all materials at 70 °C is shown in Figure 3a; a full data set can be found in Figure S5 (Supporting Information). Indeed, Figure 3a clearly shows enhanced retention with changing the alkyl chain length from 18 to 6 carbon atoms.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…[35] The grazing-incidence WAXS (GIWAXS) measurement results for BTA-C10 and BTA-C18 also evinced the disordered nature of the materials, especially those having long alkyl chains. [50] More evidence for increasing order with shorter side chains discloses if we fit the experimental switching time using the Vopsaroiu theory (Equation (S2), Supporting Information) with the experimental values of the energy barrier, remnant polarization, and coercive field, keeping the attempt frequency constant at ν 0 = 15.7 THz. The extracted critical domain size grows from 15 to 60 molecules, comparing BTA-C18 and BTA-C6.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…31 Differently to the conventional liquidcrystalline materials used for electrooptical applications, BTA maintains its macrodipole orientation at zero external field due to p-p stacking and hydrogen-bonding, which allows it to keep the polarization for up to 10 years at room temperature. [31][32][33] The overall performance of thin-film BTA capacitor devices is comparable to devices based on P(VDF-TrFE), additionally offering some advantages like lower processing temperatures, easy chemical tuning and a wider operational temperature window. 31,34,35 In this study we present interferometrically measured converse piezoelectric response in solution-processed thin-film BTA capacitor devices.…”
Section: Introductionmentioning
confidence: 99%
“…50,52,57,[73][74][75] Both BTA and PCA exhibit a LC phase at room-temperature and have been studied for their ferroelectric behaviour experimentally. 52,64,65,76,77 Atomistic MD simulations revealed that BTA in its LC phase displays a reversal of handedness of the hydrogen bond helices upon reversal of electric eld applied in a fashion akin to that in ferroelectric experiments. 78 However, such a handedness reversal was not observed in the case of PCA; 50 an electric eld reversal caused the formation of bifurcated intermolecular hydrogen bonds in the latter.…”
Section: (B)mentioning
confidence: 98%
“…Benzene-1,3,5-tricarboxamide (BTA) is a well known molecule in supramolecular polymers, due to its ease of synthesis and wide variety of applications. 4,[59][60][61][62][63][64][65][66] While its aromatic core is a simple phenyl ring, the linker is an amide group possessing an electric dipole moment arising out of the large electronegativity difference between the N-H hydrogen and the carbonyl oxygen. The structure of the molecule is shown in Fig.…”
Section: One Dimensional (1d) Polymersmentioning
confidence: 99%